LANGUAGE AGGRESSION ON THE INTERNET - CALL MORAL IMPERATIVES - Irina V. Vasenina; Tatyana N. Kukhtevich (Moscow Polytechnic University, 2016)
Virtual communication plays increasingly important role in daily life. As long as the Internet develops, it shapes out its own rules, customs and norms of interaction. For millions of people social networks became a socio-cultural environment, where they perceive social values and standards. However, these standards, unfortunately, are not always correlate with moral and legal norms. Among all kinds of Internet resources, networks placing defamatory, false or hostile information towards other individuals or groups (so called intolerant online communities) have been widely spread. The researchers most commonly associate deviant or aggressive behavior of Internet users with social networks. In this articlewe consider electronic verbal aggression towards users or groups of users of the Internet.